Pengaruh Media Pembelajaran Kintar (Kincir Pintar) Terhadap Keterampilan Membaca Pada Materi Keluargaku Unik di SDN 222 Palembang - Puspita, Nimas Della; Octaria, Dina; Masnunah, Masnunah (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The problem in this study is whether there is an influence of the learning media (kintar) of the smart wheel on reading skills in my unique family material at SD Negeri 222 Palembang? The purpose of the study was to find out whether there was an influence of smart pinwheel learning media on the reading skills of my family's unique materials at SD Negeri 222 Palembang. The research used is a quantitative method that is experimental in nature. The data collection techniques used in this study are observation, test and documentation. Based on the research, it was obtained that there was a significant influence in the use of KINTAR media on student learning outcomes in the unique family material of grade II SD N 222 Palembang. This shows that the use of KINTAR media during the learning process is very useful and student learning outcomes have also improved. With this KINTAR media, initially, the learning outcomes of students on my unique family material can be significantly increased.